The Effect of ClassPoint Learning Media as Interactive and Fun Learning - Soybatul Aslamiah Ritonga; Sahbuki Ritonga; Uswatun Hasanah Masra Tangse; Dwina Putri; Amaliah Ritonga; Wahyu Azhar Ritonga (CV. AFDIFAL MAJU BERKAH, 2023)
The era of the industrial revolution, which was all technological, made all aspects continue to innovate so that they remained optimal, especially in the world of education. The current educational challenge is that there is still a lack of more interactive learning media using ICT, so that educators or teachers must be more extra in mastering technology in the manufacture and development of learning media. This study aims to develop learning media using classpoints that are easier on learning materials taught by each educator. With the same explanation as the previous ppt media with this feature there are many things to develop, especially in questions that the teacher can directly make on slides with various types of answers. The research model used applies ADDIE (Analysis, Design, Development, Implementation, and Evaluation) with a quantitative descriptive approach using interviews and questionnaires. A total of 36 students were the subjects in this study. With the results of the study showing that students answered above the range > 60% to 100%, it means that students agree to strongly agree that classpoint learning media is fun and interactive and easy to use.